The seepage flow characteristics of hydrophobically associated polymers with different aggregation behaviours in porous media. Issue 1 (22nd January 2020) - Shi, Leiting; Zhu, Shijie; Ye, Zhongbin; Zhang, Jian; Xue, Xinsheng; Zhao, Wensen
Abstract : The polymer solution for oil displacement is subjected to strong shear action in practical application, and this action will affect its percolation characteristics in porous media. The effects of mechanical shearing on the solution properties and seepage characteristics of modified hydrophobically associated polymers and dendrimers with two different aggregation behaviours were studied. The results showed that mechanical shearing did not affect hydrophobic microzones. Polymers can re-associate to restore part of the network structure, thereby improving shear resistance (dendritic hydrophobically associating polymers > hydrophobically modified partially hydrolysed polyacrylamide). Polymers with 'cluster' aggregation behaviour enhanced solution performance, enabling them to establish higher resistance coefficient (RF) and residual resistance factor (RRF) in porous media but also bringing about injection difficulties. Increasing the injection rate would increase the injection pressure, but the established RF and RRF showed a downward trend. Mechanical shear pretreatment effectively improved the injectability of the polymer. To achieve polymer injection and flow control, pre-shearing polymer solution and low-speed injection can be used in field applications.